Analysis of Distribution Characteristics and Influencing Factors of Ambient Temperature Field in Buildings - Jin Xu; He Yue; Liu Shi; Liu ZhongYan; Liu Pei (E3S Web of Conferences, 2022)
To address the uneven distribution of the thermal environment in buildings and the temperature deviation between the end temperature sensing devices and the thermal environment of the work area, this paper presents a simulation and experimental study of the indoor temperature distribution characteristics and its influencing factors, taking an office in a northern area as the research object. Firstly, a three-dimensional model of the building is constructed based on ANSYS software to simulate the indoor temperature distribution characteristics in summer and winter under the influencing factors of outdoor environment, building orientation, window-to-wall ratio (WWR), and the form and arrangement of indoor terminals. Secondly, based on the simulation and experimental data, the effect of different influencing factors on indoor temperature is analysed, and a formula for fitting the WWRto indoor temperature and a formula for fitting the temperature deviation between the temperature sensor and the working area with the characteristics of influencing factors is proposed, laying a theoretical foundation for indoor temperature end control technology.